IMPLEMENTATION OF MERDEKA CURRICULUM AS THE NATIONAL CURRICULUM BASED ON REGULATION OF THE MINISTER OF EDUCATION, CULTURE, RESEARCH AND TECHNOLOGY NUMBER 12 OF 2024: A CONCEPTUAL REVIEW AND ITS IMPLICATIONS FOR EDUCATIONAL INSTITUTIONS IN INDONESIA (LITERATURE REVIEW METHOD) - Gunawan Widjaja; Songga Aurora Abadi; Rajes Khana (International Journal of Teaching and Learning, 2025)
This research aims to examine the implementation of Merdeka Curriculum as the national curriculum based on the Minister of Education, Culture, Research, and Technology Regulation Number 12 of 2024, and analyse its implications for educational institutions in Indonesia. The method used is a literature study with a descriptive qualitative approach, collecting and analysing various secondary sources such as official government documents, scientific journals, articles, and related research reports. The study results show that Merdeka Curriculum emphasises flexibility, autonomy and relevance of learning to the needs and potential of learners. This curriculum provides more space for schools and teachers to develop innovative, contextual, and character-strengthening-centred learning through the Pancasila Student Profile strengthening project. However, its implementation faces challenges in the form of human resource readiness, limited infrastructure, and the need for continuous training and mentoring. The successful implementation of the Merdeka Curriculum is highly dependent on the collaboration and commitment of all education stakeholders. Overall, the Merdeka Curriculum has the potential to improve the quality of national education and form a generation that is adaptive, creative, and has strong character, provided that the existing challenges can be overcome systematically and sustainably.